2019
DOI: 10.32604/phyton.2019.08244
|View full text |Cite
|
Sign up to set email alerts
|

The Allelopathic Effects of Sunflower and Wheat Root Exudates on Sinapis arvensis and Sinapis alba

Abstract: In this study, we aimed to investigate the allelopathic effects of sunflower and wheat root exudates on the common weeds such as wild mustard and white mustard in our region. The root exudates which were obtained by soaking 8 weeks old sunflower and wheat seedlings (20 or 40 seedlings) in 100 mL of distilled water for 3 days were applied to the leaves of wild mustard and white mustard. In order to compare the allelopathic effect, the recommended dose (1 g.da -1 ) and twice the recommended dose (2 g.da -1 ) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…On the contrary, both extract concentrations showed a significant increase in the contents of free amino acids, total proteins and soluble carbohydrates, especially with the 100% concentration. In line with our results, Unal et al [81] reported a concentration-dependent increase in total protein content in white mustard leaves in response to the treatment with sunflower and wheat root exudates. Similarly, the increase in free amino acid content has been reported in several plant species; P. oleracea leaves after the treatment with Rumex dentatus leaf extract [82] and R. dentatus as a result of Withania somnifera root extract treatment [83].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the contrary, both extract concentrations showed a significant increase in the contents of free amino acids, total proteins and soluble carbohydrates, especially with the 100% concentration. In line with our results, Unal et al [81] reported a concentration-dependent increase in total protein content in white mustard leaves in response to the treatment with sunflower and wheat root exudates. Similarly, the increase in free amino acid content has been reported in several plant species; P. oleracea leaves after the treatment with Rumex dentatus leaf extract [82] and R. dentatus as a result of Withania somnifera root extract treatment [83].…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, only high extract concentrations (75% and 100%) induced a significant decline in the enzymatic activities of both CAT and APX. The stimulation of CAT and APX by the low concentrations and their inhibition by the high ones could be explained by the hormesis phenomenon, where allelochemicals induce hormesis (growth enhancement) at low doses [14,100], which is supported by the results of Unal et al [81], Hua et al [101] and Hong et al [102]. It is also commonly believed that allelochemicals enhance the content of non-enzymatic antioxidants [103].…”
Section: Discussionmentioning
confidence: 78%